Physical-layer network coding in k-users MIMO-Y two-way relay channels - Tao WANG; Yong WANG; Yue ZHANG (Tongxin xuebao)
In order to exchange information among k users using the technology of physical-layer network coding in the multiple input multiple output Y two-way relay channels,the GSA-GSA scheme was proposed,using the technology of general signal alignment during the uplink and the downlink.The signals were exchanged between every source node align in a transformed subspace,rather than the direct subspace.This was realized by jointly designing the precoding matrices at all source nodes and the processing matrix at the relay.The constraints of the number of sending and receiving antennas and the sum rate of proposed scheme were analyzed.In simulation,it can figure out that the proposed scheme needs fewer antennas in the whole system and can improve the achievable system sum rate under the same SNR and degrees of freedom.